Population structure and accompanying biota of the snail Turbo (Callopoma) funiculosus (Gastropoda: Turbinidae), on Socorro Island, Revillagigedo Archipelago, Mexico - E. Holguin Quiñones, Oscar (2006)
The porcelain snail, Turbo funiculosus, is a potential fishery resource that almost has not been studied or used commercially. In March of 1992, we sampled T. funiculosus in Bahía Binners and Bahía Blanca, Socorro Island, Revillagigedo Archipelago, using 25 m2 quadrants. We found that total length varies between 3.0 and 85 mm, proportional weight between 3.0 and 228 g, and density between 6.21 and 9.87 ind/m2. The largest organisms (over 50 mm) contain 30.6 % of soft parts. Porcelain snail populations remain unexploited on Revillagedo Archipelago and could be a potential resource under an adequate management strategy.